2019
DOI: 10.1186/s12885-019-5917-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of TGF-β in lung cancer: systematic review and meta-analysis

Abstract: Background Lung cancer is the most important cause of cancer-related deaths worldwide and the overall survival of patients with non-small cell lung cancer has not improved. Transforming growth factor beta or TGF-β is a polypeptide member of the transforming growth factor beta superfamily of cytokines, while far fewer clinical studies addressing the association between TGF-β expression and the disease prognosis have been reported up to now. Therefore, our meta-analysis aims to determine the prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 29 publications
2
50
0
Order By: Relevance
“…However, the activation of TGF-β signaling pathway is suppressed in SCLC cells [59]. Recently, Li et al analyzed eight studies involving 579 patients with lung cancer and concluded that high TGF-β expression as an indicator of poor survival [60].…”
Section: Discussionmentioning
confidence: 99%
“…However, the activation of TGF-β signaling pathway is suppressed in SCLC cells [59]. Recently, Li et al analyzed eight studies involving 579 patients with lung cancer and concluded that high TGF-β expression as an indicator of poor survival [60].…”
Section: Discussionmentioning
confidence: 99%
“… 20 In addition, several EMT-inducing factors, such as E-cadherin, transforming growth factor-β, and FOX proteins, could help predict prognosis in patients with cancer. 5 , 6 , 21 , 22 According to some previous studies, among these predictors, the FOX proteins, including FOXM1, FOXQ1, FOXF1, FOXC1, FOXA1/2, and FOXO3a, are involved in tumor metastasis by mediating EMT. 5 Indeed, the prognostic impact of FOXC2 has been well documented in different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Although recognized as a tumor suppressor factor for healthy cells and early-stage cancer cells, in late-stage cancer TGF-β becomes the archetype of the tolerogenic tumor milieu, by primarily controlling the commitment and effector functions of immune cell subsets within the TME [ 102 , 103 ]. In this regard, TGF-β signaling represents a negative hallmark for many tumors and its activation has been linked with poor prognosis in colorectal [ 104 ] lung [ 105 ], breast [ 106 ] cancers, among others. Fundamentally, TGF-β can act by directly inhibiting anti-tumor immunity while sustaining the phenotype and function of pro-tumoral immune cells.…”
Section: Immune Cells Tgfb-induced Metabolismmentioning
confidence: 99%